FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS KONSUMEN (Studi Kasus pada Pasar Bu - Darman, Dian Martha; Restuhadi, Fajar; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Pasar Buah Sudirman is a well-known fruit-store in Pekanbaru. However, to gain the loyalty of shoppers, Pasar Buah Sudirman must appeal to consumers’ social motives and experiential needs, not simply provide access to desired goods. In response to changing consumer needs, the store has grown larger and metamorphed into a convenience of one-stop shopping, to include service outlets and providing daily needs goods, not only fruits, at the store. Therefore, research was aimed to study: (1) the factors that configuring customer satisfaction in Pasar Buah Sudirman, (2) what factors that configuring customer’s loyalty of Pasar Buah  Sudirman.  This research was held in two months between May – July 2014. This research was performed by applying convenience random sampling method. The sample size was 150 respondents that shopped more than twice to the targeting store. Data were analyzed by principle component analysis (PCA). The results show from 24 attributes used in the analysis of components of PCA with factor analysis are adequate for further analysis as the 'key factors' to represent the characteristic profile of Pasar Buah Sudirman’s costumers. The 8 variables, then, can be classified as: Product Quality, Reliability, Responsiveness, Assurance, Tangible, Empathy, Costumers' satisfaction, and Costumers' Loyalty, consistent with previous researches. Other findings from this research were:  (1) the respondents were satisfied with the decision to shop and never complain with product. (2) the factors that configuring costumer’s loyalty were respondents determination to shop in Pasar Buah Sudirman, retention, repetition and referral to others. Key word: satisfaction, loyality, factor analysis